Prevention of H-Aggregates Formation in Cy5 Labeled Macromolecules - Jing Kang; Oliver Kaczmarek; Jürgen Liebscher; Lars Dähne (International Journal of Polymer Science)
H-aggregates of the cyanine dye Cy5 are formed during covalent linkage to the cationic macromolecule Poly(allylamine) (PAH). The nonfluorescent H-aggregates strongly restrict the usage of the dye for analytical purposes and prevent a quantitative determination of the labeled macromolecules. The behavior of the H-aggregates has been studied by investigation of the absorption and fluorescence spectra of the dye polymer in dependence on solvent, label degree and additional sulfonate groups. H-aggregate formation is caused by an inhomogeneous distribution of the Cy5 molecules on the polymer chain. The H-aggregates can be destroyed by conformational changes of the PAH induced by interactions with polyanions or in organic solvents. It has been found that the polymer labeling process in high content of organic solvents can prevent the formation of H-aggregates. The results offer a better understanding and improvement of the use of the Cy5 dye for labeling purposes in fluorescence detection of macromolecules.